Centring healing: reflexivity, activism and the decolonial act of researching communities existing on the margin - Chirape, Skye R. Tinevimbo (PINS-Psychology in Society, 2021)
This paper introducing innovative, creative, and decolonial research methodology is part of the ongoing reflexivity of a PhD currently underway. I provide insight into the development of the research through which I reflexively present my thoughts, as a decolonial feminist psychology researcher conducting research with African LGBT individuals seeking asylum in the UK. I engage with concepts of reflexivity, activism, decolonisation, and autoethnography, as they are played out within the research process. The paper reflects on three integrated theories underpinning the study, Trauma Theory (Mollica, 2006), Structural Intersectionality Theory (Crenshaw, 1989; Brotman 2013), Afrocentric Decolonizing Kweer theory (Sharif “Herukhuti” Williams, 2016), and the decolonial methodologies proposed for the PhD research. The theories used are a deliberate effort to depart from a Eurocentric way of conducting academic research. Foregrounding reflexivity, I offer my research as a deeply political, ethical, moral, and decolonial act that can remedy researched communities. It is uncommon for PhD scholars to offer, for journal publication, meditations about a PhD project that is still underway. Yet such knowledge is also valuable. Thus, the reflexive paper serves as a demonstration of a social justice agenda for conducting the doctoral research, a decolonial act in itself.